Sound Effect Sebagai Pendukung Suspense pada Film Ready or Not - Andrian Feri Dwi Yanto Andrian (Journal of Art, Film, Television, Animation, Games and Technology, 2023)
Sound effect is one of the audio elements that acts as a support for the formation of a reality of a scene in a movie. The application of sound effects can be used to support the emergence of tension in the movie. The purpose of this research is to find out and prove that sound effects in the movie Ready or Not can support the emergence of suspense. Ready or Not is a movie with a horror genre released in 2019. This research uses Louis Gianneti's audio theory as the main theory on how pitch, volume, and tempo can support suspense in movies. The type of research used is qualitative with a descriptive approach. The material object used as a data source in this study is Ready or Not film . According to this research, the results show that the higher the pitch, the louder the volume, and the faster the tempo of the sound effect can support the emergence of suspense in the movie Ready or Not.